Pharmacoeconomic Analysis Of Using Cephalosporin Group In Appendicitis Prophylactic In Rumah Sakit Umum Daerah Subang - Yulia Wardati; Dytha Andri Deswat; Zainal Muttaqin (Fakultas Farmasi Universitas Pancasila, 2018)
The administration of cephalosporin group antibiotics in patients with post-surgical appendicitis is necessary to prevent postoperative wounds. This pharmacoeoconomic study was conducted retrospectively in the period of 1 January to 31 December 2015 in RSUD Subang for the purpose of determining the effectiveness of drugs and the cost of antibiotic use of ceftriaxone, cefotaxime, and ceftizoxime injection by Cost Effectiveness Analysis method. The subject of the patient was 78 people. Based on Average Cost Effectiveness Ratio (ACER), the smallest value is ceftriaxone Rp 729.124 / day, while the result of Cost Effectiveness plane with cefotaxime as standard drug, ceftriaxone occupies quadrant IV and ceftizoxime occupies quadrant I. The result of Incremental Cost Effectiveness Ratio (ICER) calculation obtained by difference of value equal to Rp 106.347 / day hence can be concluded that antibiotic injection of cefotaxime as standard injection antibiotics used by RSUD Subang can be replaced by antibiotic injection of ceftizoxim by adding cost Rp 106.347 / day but need attention to resource especially funds owned and should be selected if sufficient resources are available.